A global ab initio dipole moment surface for methyl chloride. (November 2016) - Owens, Alec; Yurchenko, Sergei N.; Yachmenev, Andrey; Tennyson, Jonathan; Thiel, Walter
Abstract: A new dipole moment surface (DMS) for methyl chloride has been generated at the CCSD(T)/aug-cc-pVQZ(+d for Cl) level of theory. To represent the DMS, a symmetry-adapted analytic representation in terms of nine vibrational coordinates has been developed and implemented. Variational calculations of the infrared spectrum of CH3 Cl show good agreement with a range of experimental results. This includes vibrational transition moments, absolute line intensities of the ν 1, ν 4, ν 5 and 3 ν 6 bands, and a rotation–vibration line list for both CH3 35 Cl and CH3 37 Cl including states up to J =85 and vibrational band origins up to 4400 cm −1 . Across the spectrum band shape and structure are well reproduced and computed absolute line intensities are comparable with highly accurate experimental measurements for certain fundamental bands. We thus recommend the DMS for future use. Abstract : Highlights: New high-level ab initio dipole moment surface for methyl chloride. Rigorously tested against a range of experimental results. Computed absolute line intensities comparable with highly accurate experimental measurements for certain fundamental bands. Missing band identified in HITRAN. DMS performs well for weaker bands.